Kebinekaan Agama dan Budaya dalam Tafsir Al-Iklīl Fī Ma‘ānī Al-Tanzīl - Fahma Maulida; Ahmad Zainal Abidin (ILMU USHULUDDIN, 2020)
This paper contains a study of the dynamics of Miṣbāḥ Muṣṭafa interpretation of the verses of the Qur’an in the theme of religious diversity in the interpretation of al-Iklīl fī Ma‘ānī al-Tanzīl. The dynamics are seen in the interpretation of the verse about the status of heresy and safety of non-Muslims in the hereafter. Besides explaining the interpretation of the issues related to the above problem, this paper also wants to explore further the interpretation of Miṣbā ḥ Muṣṭafā about religious diversity, which in its interpretation on one side of the mind is still relevant to the context of Indonesian social relations. But on the other hand it contradicts him. With the descriptive-explorative method, this paper discovers four principles of religious diversity in Tafsir al-Iklīl, namely: 1) diversity as sunnatullāh, as illustrated in the Misbah interpretation which believes in diversity such as Muslims and non-Muslims. 2) Islamic recognition of the existence of other religions, which is reflected in the absence of coercion in choosing religion as its belief. 3) the ability of non-Muslims to ask for protection from Muslims, and 4) religious tolerance, reflected in the absence of prohibitions to their followers to do good and fair to non-Muslims as long as they do not do bad and denounce the religion of Islam.